Utilizing Organic Waste to Create Charcoal Briquettes as a Substitute Fuel - Aldi F. Uke; Sitti Rahmawati; Magfirah Magfirah; Afadil Afadil; Dewi Salmita; Vivi D. A. Sangkota (Jurnal Akademika Kimia, 2026)
The generation of organic waste at SMA Negeri 1 Palu is substantial, and it is predominantly disposed of in landfills, leading to environmental concerns and the underutilization of potential resources. This study proposes converting organic waste into charcoal briquettes as a sustainable alternative for waste management and energy production. The objective of this research is to evaluate the composition and physicochemical properties of charcoal briquettes produced from organic waste generated at SMA Negeri 1 Palu. The briquettes were prepared from collected organic waste and characterized using standard fuel-quality parameters. The results showed that the produced briquettes exhibited a calorific value of 4385 cal.g-1, density ranging from 0.75 to 0.86 g.cm-3, and a combustion rate of 0.25 g.s-1. In addition, the moisture content, ash content, volatile matter, and fixed carbon were 7.5091%, 5.5894%, 16.1316%, and 78.279%, respectively. These findings indicate that organic waste-derived briquettes possess acceptable fuel characteristics and demonstrate potential as an alternative renewable energy source. This study highlights a practical approach to reducing organic waste while simultaneously generating value-added energy products, particularly in educational institutions.